2020
DOI: 10.1182/blood.2019003293
|View full text |Cite
|
Sign up to set email alerts
|

Sequential CD19-22 CAR T therapy induces sustained remission in children with r/r B-ALL

Abstract: Pan and colleagues report one of the first prospective evaluations of planned sequential chimeric antigen receptor (CAR) T-cell therapy targeting CD19 and then CD22 in a phase 1 trial, indicating acceptable toxicity and encouraging durable efficacy in pediatric patients with relapsed/refractory (r/r) acute lymphoblastic leukemia (ALL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 17 publications
(35 reference statements)
0
91
0
1
Order By: Relevance
“…To address the possible causes of recurrence after CAR-T cell treatment and to improve long-term outcome, a cohort of studies and clinical trials have been conducted. These involved dual-signaling CAR-T cell therapies and preventive infusion of a second CAR-T cell product targeting a different antigen when a significant and sustained decline of copies of previous CAR-T cells was detected before the possibility of relapse [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…To address the possible causes of recurrence after CAR-T cell treatment and to improve long-term outcome, a cohort of studies and clinical trials have been conducted. These involved dual-signaling CAR-T cell therapies and preventive infusion of a second CAR-T cell product targeting a different antigen when a significant and sustained decline of copies of previous CAR-T cells was detected before the possibility of relapse [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The situation was extremely difficult in our two patients who already displayed failed allogeneic HSCT with prior GvHD. Tong and Wu et al, who led the cell therapy team in Beijing Boren Hospital, have demonstrated that CD22-CAR-T cell therapy was as effective as CD19-CAR-T cell therapy, and sequential CD19-followed by CD22-CAR-T cell therapies may prevent immune escape, resulting in prolonged response 9,10 , which was applied in Case 1 because higher expression of CD22 on leukemic cells was found. However, because of the lack of CD22 in Case 2, only CD19-CAR-T could be reasonably prepared.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrate the feasibility of sequentially administering CD19 CAR T cells followed by CD22 CAR T cells alongside the safety, toxicity, and efficacy of such a model. 1 Their observation suggests that sequential CAR T-cell targeting strategies may be safe and effective and provides proof-of-concept of a potential strategy that may allow for dual-antigen CAR T-cell targeting.…”
Section: The One-two Punch (Of Car T Cells)mentioning
confidence: 98%